1989
DOI: 10.1152/ajpheart.1989.256.5.h1509
|View full text |Cite
|
Sign up to set email alerts
|

Anti-EDRF effect of tumor necrosis factor in isolated, perfused cat carotid arteries

Abstract: Cat carotid arteries that have an intact endothelium were isolated and perfused with Krebs-Henseleit solution containing recombinant human tumor necrosis factor (rhTNF). Perfused arteries were preconstricted with KCl and then dilated with acetylcholine (ACh) or acidified NaNO2. After perfusion with TNF (4 micrograms/ml) for 120 min, the ACh-induced vasodilator response was markedly blunted, but the NaNO2 vasodilator response was not significantly affected. Arteries perfused with 2 micrograms/ml TNF for 60-120 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 0 publications
4
42
0
1
Order By: Relevance
“…However, as we found that the endothelium played a protective role and was not the primary mediator of the harmful effect of LPS-activated macrophages, the L-arginine pathway ofthe endothelium was unlikely to have been involved in contractility depression. This is corroborated by in vitro studies showing that LPS and monokines reduce EDRF release (47,52,53). In the present work, similar protection against LPS-activated macrophages was observed in both deendothelialized and intact arteries exposed extraluminally to LNMMA.…”
Section: Discussionsupporting
confidence: 90%
“…However, as we found that the endothelium played a protective role and was not the primary mediator of the harmful effect of LPS-activated macrophages, the L-arginine pathway ofthe endothelium was unlikely to have been involved in contractility depression. This is corroborated by in vitro studies showing that LPS and monokines reduce EDRF release (47,52,53). In the present work, similar protection against LPS-activated macrophages was observed in both deendothelialized and intact arteries exposed extraluminally to LNMMA.…”
Section: Discussionsupporting
confidence: 90%
“…Sci. USA 90 (1993) endothelium-derived nitric oxide (24,25). The significance of preserving nitric oxide extends far beyond maintaining the ability ofthe vasculature to dilate, since endothelium-derived nitric oxide also exerts anti-aggregation actions in platelets (26) and anti-adherence effects in neutrophils (27) and quenches superoxide radicals (28).…”
Section: Discussionmentioning
confidence: 99%
“…51,52 In the setting of atherosclerosis in which steady-state eNOS mRNA has been shown to be downregulated, 9,10 the contribution of TNF-␣ may be crucial to the pathogenesis of the disease. Some of the earliest published studies of eNOS gene regulation identified modulation of mRNA stability as a regulatory target of pro-inflammatory cytokines.…”
Section: Tnf-␣ and Lipopolysaccharidementioning
confidence: 99%